KELIMPAHAN DAN NISBAH KELAMIN SIPUT BAKAU (Telescopium telescopium) DI EKOSISTEM MANGROVE DESA DARUL AMAN KECAMATAN RUPAT KABUPATEN BENGKALIS - Efriyeldi, Efriyeldi; Zulkifli, Zulkifli (Jurnal Perikanan dan Kelautan, 2015)
Mangrove ecosystem in the coastal of Darul Aman Village has been seriously degradated. This condition can affect gastropods live in the area. The purpose of this study was to determine the density and sex ratio of mangrove snails Telescopium telescopium in mangrove ecosystem. This study was conducted in September 2014 in the mangrove ecosystems of Darul Aman Village Rupat Distric. The method used in this study was a survey method. Location study was divided into three stations. Snail T. telescopium sample was collected by hand-picking directly in five plots of 2 m x 2 m for each station. The snail sex determination was done from colour and shape observation of gonad in laboratory. Variance Analysis (ANOVA) was used to test the significance differences of mangrove snail density between stations. During the research, a total of 77 samples of snail mangroves, with sizes ranging from 59.0 to 98.1 mm and a weight of 24.83 to 84.26 g was obtained. Average density of mangrove snails obtained 0.60±0.379 to 2.05±0.411 (ind/m2). Mangrove snail density was significantly different between stations (sig.<0.05). Morisita index value at the third station shows that the distribution pattern of mangrove snail is uniform (Id <1.0). Sex ratio (male and female) of mangrove snails was 1: 1.